Joyce Carol Oates
Doctor Martha Heasley Cox, Joyce Carol Oates, and Doctor Paul Douglass on the occasion of Ms. Oates's presentation for the Martha Heasley Cox Lecture series. Photo taken in MHCCfSS, at the Center's 3rd location in portables.